STRATEGI ADMINISTRASI DAN MANAJEMEN UMKM DALAM MENGHADAPI PERSAINGAN DI PASAR LOKAL PANDEGLANG - Lukman Hakim, Agus; Handoko, Pryo; Nugroho, Arif; Jumanah, Jumanah; Abdul Halim, Ibrohim (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to explore the administration and management strategies implemented by MSMEs in Pandeglang Regency in facing competition in the local market. The approach used is qualitative with a case study design, where data is collected through interviews, participant observation and documentation. Research findings show that many MSMEs in Pandeglang face challenges in administrative management, such as dependence on manual systems and lack of technological literacy. Human resource (HR) management is also limited to basic skills without further training. Apart from that, although several MSME players have used social media for marketing, the use of technology for operational management is still minimal. Recommendations from this research include the need for continuous training, mentoring, and access to technology that can increase the efficiency and competitiveness of MSMEs. This research provides important insights for developing policies that support MSMEs at the local level, especially in facing increasingly competitive market dynamics.